Biodegradation of Polyethylene Using Bacillus Subtilis. (2016) - Vimala, P.P.; Mathew, Lea
Abstract: Polyethylene is among the major plastics being dumped in the environment. The study explores methods to enhance the rate of biodegradation of polyethylene using physical and biological means. Bacterial species – Bacillus subtilis – was tested for its potential in utilizing polyethylene as their sole carbon source. The microbial species produced surface active compounds (Biosurfactants) that enhance the degradation process. Pretreatment of polymer films with Ultraviolet radiation aids its accessibility as food for the microorganisms thus enabling a much faster rate of biodegradation. Inoculation of pretreated polyethylene films of thickness 18 μ with Bacillus subtilis with the addition of its biosurfactant (surfactin) proved to be most efficient with a weight loss percentage of 9.26% in 30 days